Airway Management and Clinical Outcomes in External Laryngeal Trauma: A Case Series. (August 2019) - DePorre, Alexandra R.; Schechtman, Samuel A.; Hogikyan, Norman D.; Thompson, Aleda; Westman, Amanda J.; Sargent, Richard A.; Rosko, Andrew J.; Bauer, Ashley; Shanks, Amy M.; Kupfer, Robbi A.; Healy, David W.
Abstract : External laryngeal trauma is a rare but potentially fatal event that presents several management challenges. This retrospective observational case series conducted at a level-1 trauma center over a 12-year period consists of 62 cases of acute external laryngeal trauma. Patient demographics, mode and mechanisms of injury, presenting signs and symptoms, initial imaging results, airway management, time to surgical management, and 6-month outcomes including airway status, deglutition status, and voice quality were investigated. No difference was found in mortality or 6-month outcomes between patients requiring surgical repair and/or tracheostomy versus patients with less severe injuries managed conservatively.